Implementing knowledge management in academic libraries : a comparative case study of the Kamuzu College of Nursing and Bunda College of Agriculture libraries - Namondwe, Trevor (Library and Information Studies Centre (LISC), 2015)
Includes bibliographical references (p. 133-138).